Development of a Wideband and High Gain ESIW H-plane Horn Antenna - Seyd Hossein Haghirosadat; Mohammad Neshati (AUT Journal of Electrical Engineering, 2022)
In this paper, a new structure of an Empty Substrate Integrated Waveguide (ESIW) H-plane Horn Antenna with improved gain and impedance bandwidth is introduced. Using ESIW technology, by removing the dielectric material of the SIW structure, the dielectric loss is eliminated and in turn, antenna gain is improved. The flaring area of the ESIW horn is also divided into a few rectangular waveguide sections with proper length and width to improve its impedance bandwidth. Moreover, adding radiating slots significantly reduce Half Power Beamwidth (HPBW) of the E-plane pattern of the ESIW horn. In addition, by adding a slot array at the right position of the structure, the radiating fields of both the horn aperture and the slot array are properly combined and in turn, radiation performance of the ESIW horn is improved. Additionally, by adding non-radiating slots on both sides of the structure, impedance bandwidth is significantly enhanced. The most important feature of the proposed horn antenna is its two-dimensional (2-D) structure, while both gain and impedance bandwidth are improved. The introduced horn antenna is successfully simulated by High Frequency Structure Simulator (HFSS) software and the results are verified by CST. The obtained results show that it provides 14.1 dBi gain with 98% radiation efficiency and 11.3% impedance bandwidth over the frequency range of 25.5 GHz up to 28.5 GHz.